TRENDS TOWARDS STRONGER DATA PROTECTION: THE RIGHT TO BE FORGOTTEN IN THE EUROPEAN UNION - Nikolaos Koutras (European Scientific Journal, ESJ, 2014)
Access to knowledge is crucial for the flourishing of knowledgeeconomies, the economies of the future. Information resources and data aremajor knowledge assets, generally and especially in the case of scholarlycommunications.This paper illustrates the significance of an alternative legislative and/or soft law framework on the regulation specifically of the development andinformation access within the European Union.By its dimension, ambition and complexity, the Lisbon Strategy -also known as the Lisbon Agenda or Lisbon Process - constitutes one of themost far-reaching political initiatives to have been embarked upon over thelast decade. At the Lisbon European Council in 2000 the European Union setitself a new strategic goal for 2010, a goal which consisted of a global andlong-term agenda of reform and modenisation.The subject matter of this paper is grounded on the key question ofthe appropriate equilibrium between copyright law and data protection inrelation to informational resources, among European institutions, accordingto European regulations and recommendationsTaking everything into account, it is undeniable fact that currentEuropean legislation and its framework concerning data protection should beshifted. In particular, such a framework might in its turn help however littletowards securing the widest possible protection of human rights forEuropean people.